2020
DOI: 10.1186/s12885-020-06856-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of DANCR/microRNA-518a-3p/MDMA ceRNA network in the growth and malignant behaviors of colon cancer cells

Abstract: Background The competing endogenous RNA (ceRNA) networks of long non-coding RNAs (lncRNAs) and microRNAs (miRs) have aroused wide concerns. The study aims to investigate the roles of lncRNA DANCR-associated ceRNA network in the growth and behaviors of colon cancer (CC) cells. Methods Differentially expressed lncRNAs between CC and paracancerous tissues were analyzed using microarrays and RT-qPCR. Follow-up studies were conducted to evaluate the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The biological role and function of miR-518a have been identified in several cancers. For example, miR-518a overcame CDDP resistance in colon cancer by targeting MDMA [ 31 ]. Moreover, Li et al revealed that HOXA11-AS enhanced cell viability and invasion via miR-518a in oral squamous cell carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological role and function of miR-518a have been identified in several cancers. For example, miR-518a overcame CDDP resistance in colon cancer by targeting MDMA [ 31 ]. Moreover, Li et al revealed that HOXA11-AS enhanced cell viability and invasion via miR-518a in oral squamous cell carcinoma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-518a-3p inhibits colorectal cancer cell growth through targeting NF-κB-inducing kinase, 10 and knockdown of miR-518a-3p promotes colon cancer cell migration and invasion via up-regulation of murine double minute 2. 11 Our results confirmed the anti-tumor effects of miR-518a-3p against migration and invasion of TNBC, revealing its potential clinical application in TNBC. Moreover, TMEM2 was validated as a target of miR-518a-3p in TNBC.…”
Section: Discussionsupporting
confidence: 76%
“…9 MiR-518a-3p was reported to be an anti-tumor effector for colorectal cancer 10 and participates in malignant behavior of colon cancer. 11 However, the role of miR-518a-3p in TNBC remains elusive. TMEM2 (transmembrane protein 2), a single-pass transmembrane domain protein, functions as hyaluronidase to degrade hyaluronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…3.1 miR-518a-3p was downregulated in HCC tumor tissues and correlated with prognosis of HCC patients According to previous studies, a reduced expression of miR-518a-3p has been shown in CRC cells as well as CRC tissues [7,12] . Thus, in order to illustrate the correlation between miR-518a-3p expression and HCC, its expression level was detected by RT-qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%